Myocardial Contractility: Historical and Contemporary Considerations - Muir, William W.; Hamlin, Robert L. (Frontiers in Physiology, 2020)
The term myocardial contractility is thought to have originated more than 125 years ago and has remained and enigma ever since. Although the term is frequently used in textbooks, editorials and contemporary manuscripts its definition remains illusive often being conflated with cardiac performance or inotropy. The absence of a universally accepted definition has led to confusion, disagreement and misconceptions among physiologists, cardiologists and safety pharmacologists regarding its definition particularly in light of new discoveries regarding the load dependent kinetics of cardiac contraction and their translation to cardiac force-velocity and ventricular pressure-volume measurements. Importantly, the Starling interpretation of force development is length-dependent while contractility is length independent. Most historical definitions employ an operational approach and define cardiac contractility in terms of the hearts mechanical properties independent of loading conditions. Literally defined the term contract infers that something has become smaller, shrunk or shortened. The addition of the suffix “ility” implies the quality of this process. The discovery and clinical investigation of small molecules that bind to sarcomeric proteins independently altering force or velocity requires that a modern definition of the term myocardial contractility be developed if the term is to persist. This review reconsiders the historical and contemporary interpretations of the terms cardiac performance and inotropy and recommends a modern definition of myocardial contractility as the preload, afterload and length-independent intrinsic kinetically controlled, chemo-mechanical processes responsible for the development of force and velocity.